1998
DOI: 10.1185/03007999809113354
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epidermal Growth Factor (EGF) in Oesophageal Mucosal Integrity

Abstract: Oesophageal mucosa has well established protective mechanisms, which operate within pre-epithelial, epithelial and post-epithelial compartments. Since refluxed acid and pepsin always act from the luminal side of the mucosa, protective factors like EGF, operating as a part of pre-epithelial defence, are thought to be pivotal in the maintenance of the integrity of the oesophageal mucosa. The significant contribution of salivary EGF to the quality of the oesophageal mucosal barrier has been demonstrated in an exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 53 publications
1
35
0
1
Order By: Relevance
“…Interestingly, a recent study has suggested that IGFBP-3 up-regulation in oesophageal cells may be mediated by the epithelial growth factor receptor (EGFR) (Takaoka et al 2004). Epithelial growth factor (EGF) signalling is known to play a crucial role in oesophageal healing (Marcinkiewicz et al 1998), supporting, therefore, our hypothesis that IGFBPs expression may be part of the physiological response to epithelial damage.…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, a recent study has suggested that IGFBP-3 up-regulation in oesophageal cells may be mediated by the epithelial growth factor receptor (EGFR) (Takaoka et al 2004). Epithelial growth factor (EGF) signalling is known to play a crucial role in oesophageal healing (Marcinkiewicz et al 1998), supporting, therefore, our hypothesis that IGFBPs expression may be part of the physiological response to epithelial damage.…”
Section: Discussionmentioning
confidence: 61%
“…out before the present one, have established salivary and digestive tract deficiencies of protection factors, such as EGF, in individuals with dyspeptic disease or reflux esophagitis 21,22,25,26 . More recently we have established a significant reduction in EGF salivary concentration in individuals with GERD chronic laryngitis when compared to a group of normal individuals 15,16,27 .…”
Section: Resultsmentioning
confidence: 99%
“…One of the factors most responsible for homeostasis of the oral mucosa and the digestive tract is the saliva and its organic content. The Epidermal Growth Factor -EGF, is the salivary protein with the most action on epithelial regeneration after physical and chemical aggression, because of its important capacity in replicating DNA and aiding in the neoangiogenesis of epithelial cells 25 . In a recent study, we proved that there is a significant EGF concentration reduction in saliva in individuals with LPR when compared to normal individuals 27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ein anderer Wachstumsfaktor, «acidic fibroblast growth factor» (aFGF) akkumuliert während der Progression von der Metaplasie zum Karzinom [46]. Andererseits tragen Wachstumsfaktoren auch zum Schutz vor gastroösophagealem Reflux und zur mukosalen Barriere im Ösophagus bei, wie zum Beispiel EGF aus Speichel und Öso-phagusepithel [47]. Welches Equilibrium in der Expression von Wachstumsfaktoren und deren Rezeptoren physiologisch erforderlich ist, ist noch ungeklärt.…”
Section: Tumorsuppressorgeneunclassified